The Mega-MUSCLES spectral energy distribution of TRAPPIST-1 - Wilson, DJ; Froning, CS; Duvvuri, GM; France, K; Youngblood, A; Schneider, PC; Berta-Thompson, Z; Brown, A; Buccino, AP; Hawley, S; Irwin, J; Kaltenegger, L; et al. (IOP Publishing, 2021)
We present a 5 Å–100 μm spectral energy distribution (SED) of the ultracool dwarf star TRAPPIST-1, obtained as part of the Mega-MUSCLES Treasury Survey. The SED combines ultraviolet and blue-optical spectroscopy obtained with the Hubble Space Telescope, X-ray spectroscopy obtained with XMM-Newton, and models of the stellar photosphere, chromosphere, transition region, and corona. A new differential emission measure model of the unobserved extreme-ultraviolet spectrum is provided, improving on the Lyα–EUV relations often used to estimate the 100–911 Å flux from low-mass stars. We describe the observations and models used, as well as the recipe for combining them into an SED. We also provide a semiempirical, noise-free model of the stellar ultraviolet spectrum based on our observations for use in atmospheric modeling of the TRAPPIST-1 planets.